Dirty bomb radiological simulations: two explosion scenarios using the Rio 2016 Olympic games Athletes’ Village as a model - José Francisco Pereira; José Ubiratan Delgado (Brazilian Journal of Radiation Sciences, 2018)
A historic moment in terrorist bombing in the world was the explosion of the twin towers in the USA, starting a new series of attacks. The bombing brought up many concerns for security authorities all over the world. However, no study about this kind of terrorism involving Olympic venues or big events has ever been published considering dirty bombs with radiological material. This study aims to present, using US NARAC HotSpot Code, a procedure that combines two realistic potential scenarios in the event of a terrorist attack involving the explosion of a Radiological Dispersion Device (dirty bomb) that contains two radionuclides, 137Cs and 241Am, in the Olympic Village. The results are shown in terms of effective dose (E) and deposition of radioactive material in the soil, which will provide security authorities with information for immediate radiological emergency response actions in order to protect the public and emergency first responders.  This study considers a scenario with a dirty bomb explosion during the Rio 2016 Olympic Games that hosted 10,500 athletes from 205 different countries in the Olympic Village. For the calculations of this study the HotSpot code was applied, allowing for emergency response teams to predict the environmental impact depending on the radionuclide used, of the Pasquill stability class, according to the different quantities of explosive, the height of the explosion and the distance in meters from the point of the explosion. It was observed that 241Am has a higher dose level than 137Cs, while the ground deposition of 137Cs was higher.